How do people with chronic pain choose their music for pain management? Examining the external validity of the cognitive vitality model - Howlin, Claire; Walsh, Rosemary; D'Alton, Paul; Rooney, Brendan (Frontiers in Psychology, 2023)
Music interventions for pain are more successful when patients choose the music themselves (Garza-villarreal et al., 2017; Howlin & Rooney, 2021b; Lee, 2016). But little is known about the cognitive processes associate with music preferences of people with chronic pain for pain management. The Cognitive Vitality Model is a recently developed theoretical framework that outlines five cognitive mechanisms that mediate the analgesic effects of music and may help to understand how and why people choose specific pieces of music for pain management. The current study examines how people choose music for pain management and examines if people consider factors aligned with the cognitive vitality model when making this choice. In this way, this study examines the external validity of the cognitive vitality model from the perspective of chronic pain patients. Using a sequential explanatory mixed method approach, this study involved both quantitative and qualitative data collection. Seventy patients with chronic pain completed an online experiment, which asked patients to choose a piece of music for pain management and then answer a questionnaire based on the Cognitive Vitality Model in relation to this music choice. Additionally, patients completed a series of music listening trials to assess chronic pain patients’ preferences for energy levels in music. Factor Analysis identified a five-factor structure in participant responses, that was consistent with five mechanisms identified in the Cognitive Vitality Model (CVM). Analysis indicates that people with chronic pain choose music that corresponds with the factors Musical Integration and Cognitive Agency. Musical Integration refers to the degree to which the music can provide an immersive and absorbing experience. Cognitive Agency refers to having an increased feeling of control. Thematic synthesis of patient responses was used to gain more insight into how these processes mediate the analgesic benefits of music listening from the perspective of chronic pain patients. Overall, this demonstrates that people with chronic pain have specific attentional strategies that can be used to support pain management through active music listening.